Physical exercise improves mitochondrial function in ovariectomized rats. Issue 2 (21st June 2022) - Ignacio, Daniele Leão; Fortunato, Rodrigo Soares; Silvestre, Diego; Matta, Leonardo; de Vansconcelos, Andressa Lima; Carvalho, Denise Pires; Galina, Antonio; Werneck-de-Castro, João Pedro; Cavalcanti-de-Albuquerque, João Paulo
Abstract : Estrogen deficiency causes metabolic disorders in humans and rodents, including in part due to changes in energy expenditure. We have shown previously that skeletal muscle mitochondrial function is compromised in ovariectomized (Ovx) rats. Since physical exercise is a powerful strategy to improve skeletal muscle mitochondrial content and function, we hypothesize that exercise training would counteract the deficiency-induced skeletal muscle mitochondrial dysfunction in Ovx rats. We report that exercised Ovx rats, at 60–65% of maximal exercise capacity for 8 weeks, exhibited less fat accumulation and body weight gain compared with sedentary controls. Treadmill exercise training decreased muscle lactate production, indicating a shift to mitochondrial oxidative metabolism. Furthermore, reduced soleus muscle mitochondrial oxygen consumption confirmed that estrogen deficiency is detrimental to mitochondrial function. However, exercise restored mitochondrial oxygen consumption in Ovx rats, achieving similar levels as in exercised control rats. Exercise-induced skeletal muscle peroxisome proliferator-activated receptor-γ coactivator-1α expression was similar in both groups. Therefore, the mechanisms by which exercise improves mitochondrial oxygen consumption appears to be different in Ovx-exercised and sham-exercised rats. While there was an increase in mitochondrial content in sham-exercised rats, demonstrated by a greater citrate synthase activity, no induction was observed in Ovx-exercised rats. Normalizing mitochondrial respiratory capacity by citrate synthase activity indicates a better oxidative phosphorylation efficiency in the Ovx-exercised group. In conclusion, physical exercise sustains mitochondrial function in ovarian hormone-deficient rats through a non-conventional mitochondrial content-independent manner.